Length-weight relationships for four fish species from the coast of Benghazi, Libya1 - M. Said , Mona (Libyan Journal of Science &Technology, 2026)
In this short paper, we estimated length-weight relationships for four fish species off Benghazi (Oct-Dec 2023) using W = a Lb on log-transformed data and tested isometry at 0.05. Across 343 individuals, r2 ranged 0.30-0.91; b indicated isometry in L. mormyrus and M. cephalus, negative allometry in P. forsskali, and an anomalously low value in S. scriba requiring verification. These baseline support biomass conversion and regional stock assessments.